Analysis of mixing performances in microchannel with obstacles of different aspect ratios. (October 2019) - Mondal, Bappa; Pati, Sukumar; Patowari, PK
In this study, the mixing performance and pressure drop characteristics have been numerically analyzed for flow through rectangular microchannel with obstacles in the walls arranged in a staggered manner. Three different aspect ratios (AR) of the obstacles are considered, namely 4:1, 1:1, and 1:4. The effects of aspect ratio of the obstacles on the mixing efficiency and the pressure drop are analyzed and compared with that of the channel without obstacle. The results are presented in terms of Reynolds number (Re) and Schmidt number (Sc) in the following range: 0.2 ≤ Re ≤ 1 and 500 ≤ Sc ≤ 1500. Enhanced mixing efficiency is achieved for the case of microchannel with obstacles and the corresponding pressure drop is also found to be higher. The mixing efficiency as well as the pressure drop is maximum for AR = 1:4 among all the geometries considered in the analysis in same flow condition. Furthermore, for a given configuration of the microchannel the mixing efficiency is governed by the mass Peclet number and, accordingly, the mixing efficiency increases with the decrease in Schmidt number for a given Reynolds number.